Influences of girdling and potassium treatments on fruit quality and some physiological characters of ‘Fremont’ mandarin variety - Ülker Tuğba (Folia Horticulturae, 2021)
Growing citrus involves cultural treatments such as girdling and foliar potassium treatment to increase fruit size, yield and quality. The aim of the study was to evaluate the effects of single and double stem girdling, potassium nitrate (KNO3) treatment on leaves and combinations of these treatments on the fruit yield, size and quality characteristics, leaf chlorophyll concentration and leaf nitrogen content, leaf fluorescence (PSII) and leaf sugar content of the ‘Fremont’ mandarin variety. Girdling treatments were applied on the stem by removing 4 mm wide ring of bark at the end of anthesis and after the June fruit drop. Foliar KNO3 applications were applied at a concentration of 4% twice (90 days and 120 days after full anthesis) in the experiment. The single girdling (SG) and double girdling (DG) treatments on stems increased fruit yield (kg · tree−1) by approximately 40% relative to the control (C). Treatments did not significantly affect the internal fruit quality of the ‘Fremont’ mandarin variety except in fruit colour and appearance. The highest impact on fruit size was found in the DG + KNO3 treatment. According to treatments and periods, the SPAD values varied between 62.08 and 70.67, whereas the PSII values varied between 0.698 and 0.756. The treatments significantly increased the leaf nitrogen (N) concentration and the fructose, glucose and sucrose concentrations relative to the control. The highest N concentration content was detected in the foliar potassium treatment, and the highest total sugar content was detected in the SG treatment.